PENGARUH STRUKTUR GOOD CORPORATE GOVERNANCE DAN UMUR PERUSAHAAN TERHADAP INTELLECTUAL CAPITAL DISCLOSURE (Studi Empiris Pada Perusahaan Yang Tergabung Indeks LQ-45 Di Bursa Efek Indonesia 2012-2015) - Lacmy Earnest Anugrah, 12.05.52.0094; Susilowati, Yeye (Students' Journal of Accounting and Banking, 2017)
This study aims to determine the effect of board size, the number of board meetings, the size of the audit committee, the number of audit committee meetings, concentration of ownership, the life of the company and disclosure of intellectual capital This study population is a company listing on the Indonesia Stock Exchange index of LQ-45 2012-2015 sample was taken by purposive sampling method. Data were analyzed using normality skewness test, classic assumption test, coefficient determination test, test F and test the hypothesis. Test results variable board size, the number of board meetings, the number of audit committee meetings, and the concentration of ownership has no effect on the disclosure of intellectual capital. whereas the size of the negative effect on the audit committee disclosure of intellectual capital and firm age positive effect on intellectual capital disclosuresKeywords: Corporate Governance, Intellectual Capital Disclosure, The Size of The Board of Commissioners, Number of Board Meeting, The Audit Committee Size, Number of Audit Committee Meetings Shareholding Concentration, Company Age, Intellectual Capital Dislosure